Supporting open access to European academic courses: The ASK-CDM-ECTS tool - Sampson, Demetrios; Zervas, P. (2012)
Purpose: This paper aims to present and evaluate a web-based tool, namely ASK-CDM-ECTS, which facilitates authoring and publishing on the web descriptions of (open) academic courses in machine-readable format using an application profile of the Course Description Metadata (CDM) specification, namely CDM-ECTS. Design/methodology/approach: The paper examines existing open academic courses initiatives and presents a conceptual model for describing an academic course. Next, the elements of the conceptual model are mapped to the CDM specification, as well as to the CDM-ECTS application profile for describing (open) academic courses with ECTS compatible information. Finally, the ASK-CDM-ECTS tool is presented, which allows authoring of (open) academic courses descriptions based on the proposed conceptual model and by following the CDM-ECTS application profile. Findings: Based on the evaluation results, it is evident that ASK-CDM-ECTS can clearly support the process of describing academic courses offered by European Higher Education Institutions (HEIs) with ECTS compatible information following the CDM-ECTS application profile; and the process of searching and retrieving academic courses offered by European HEIs. Research limitations/implications: The evaluation scenarios were executed with users' representatives from only one HEI. Future work intends to conduct further experiments involving users' representatives from different HEIs for evaluating the proposed tool. Social implications: OpenCourseWare has become a social movement aiming to equal opportunities in education. This paper presents the ASK-CDM-ECTS tool, which can be exploited for setting-up European Open Courses Initiatives that will facilitate open access to education and learning for the societies of the EU Member States. Originality/value: Despite the development of the CDM specification for describing (open) academic courses, and of its application profile CDM-ECTS, it appears that there exists no software tool that allows authoring and publishing on the web descriptions of (open) academic courses following CDM-ECTS. Thus, in this paper, the authors address this issue by introducing the ASK-CDM-ECTS tool, aiming at describing (open) academic courses following the CDM-ECTS application profile. © Emerald Group Publishing Limited.